Signals and systems : fundamentals - Li, Gang, 1961-; Chang, Liping, 1980-; Li, Sheng, 1984- (De Gruyter textbook., 2015)
Signals and systems enjoy wide application in industry and daily life, and understanding basic concepts of the subject area is of importance to undergraduates majoring in engineering. With rigorous mathematical deduction, this introductory text book is helpful for students who study communications engineering, electrical and electronic engineering, and control engineering. Additionally, supplementary materials are provided for self-learners.